(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2014)
Statement of the problem. The features of thermal processes in the structural modules of radio-electronic apparatus -сells and microassemblies, elements of their electronic structure are reviewed. Internal thermal processes. The internal thermal processes in elements of electronic structure are considered. Efficiency factor of modules, energy efficiency indicators of resistors, capacitors, inductances based on models of equivalent two-terminalare analyzed. The basic structural elements of radioelectronic devices. The design feature of cells and mikroassemblies are considered. Thermal field of a cell and microassembly. The basic mathematical models to determine the temperatures of the elements of cells and microassemblies electronic structure are proposed. Thermal field of microassemblies is modeled, analytical equation for determin ing the temperature of all its elements is obtained. Account of temperatures of microassembly. The results of imitating modeling of temperatures microassemblies with various conditions of cooling are submitted. Software definition of temperatures for cells and microassemblies. The automated designing programs for the temperature modes account in cells and microassembly of the radio-electronic are described. Conclusions. The primary tasks performed in the work are listed.